2021
DOI: 10.1038/s41598-021-94717-0
|View full text |Cite|
|
Sign up to set email alerts
|

The association between carotid blood flow and resting-state brain activity in patients with cerebrovascular diseases

Abstract: Cerebral hypoperfusion impairs brain activity and leads to cognitive impairment. Left and right common carotid arteries (CCA) are the major source of cerebral blood supply. It remains unclear whether blood flow in both CCA contributes equally to brain activity. Here, CCA blood flow was evaluated using ultrasonography in 23 patients with cerebrovascular diseases. Resting-state brain activity and cognitive status were also assessed using magnetoencephalography and a cognitive subscale of the Functional Independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Notably, the right hemisphere plays an important role in the relationship between CSF biomarkers, hypoperfusion, and oscillatory changes in the RPt ( Stomrud et al, 2010 , 2012 ; Kramberger et al, 2013 ; Hata et al, 2016 ). We previously demonstrated that blood velocity was correlated with MF and IAF in the right common carotid artery (CCA) but not in the left CCA ( Matsumoto et al, 2021 ). This finding suggests a hemispheric asymmetry in the neuropathological mechanisms underlying AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the right hemisphere plays an important role in the relationship between CSF biomarkers, hypoperfusion, and oscillatory changes in the RPt ( Stomrud et al, 2010 , 2012 ; Kramberger et al, 2013 ; Hata et al, 2016 ). We previously demonstrated that blood velocity was correlated with MF and IAF in the right common carotid artery (CCA) but not in the left CCA ( Matsumoto et al, 2021 ). This finding suggests a hemispheric asymmetry in the neuropathological mechanisms underlying AD.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-tuned parameters may reveal associations not observed with the current settings. We did not revise the MEG oscillatory parameters because they have been used repeatedly in previous studies by us ( Haraguchi et al, 2021 ; Matsumoto et al, 2021 ; Hoshi et al, 2022 ; Hirata et al, 2024 ) and others ( Fernández et al, 2006 ; Poza et al, 2007 , 2008a , b ; Gómez et al, 2013 ), and we aimed to examine THEIR relationships to eZIS parameters, but not those of any other/new parameters. For example, the MEG oscillatory parameters can be adjusted individually; the International Federation of Clinical Neurophysiology (IFCN)–EEG research workgroup ( Babiloni et al, 2020 ) encouraged adjusting the frequency bands individually for minimising the biases on the statistical tests.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study of electrophysiological spectral signatures, measured with MEG resting state recordings, has been well-established for early detection and prognosis in neurodegenerative disorders (López-Sanz et al, 2019 ), especially for Alzheimer’s disease (López-Sanz et al, 2018 ; Nakamura et al, 2018 ) and mild cognitive impairment (MCI; López-Sanz et al, 2016 ). According to the cerebrovascular factors they can also be found in studies analyzing MEG spectral features for patients with stroke (Tecchio et al, 2006 ; Chu et al, 2015 ; Kielar et al, 2016 ; Johnston et al, 2022 ), which is one of the major causes of major VCI, even using ultrasonography measures to assess carotid blood flow (Matsumoto et al, 2021 ). Nevertheless, to the best of our knowledge, no article has been published performing spectral analysis with MEG in older people diagnosed with mild or major VCI, and only a few can be found with EEG, as described in a recent systematic review performed by our research group (Torres-Simón et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%